Outbreak of Clostridium difficile Infections at an Outpatient Hemodialysis Facility—Michigan, 2012–2013. (27th April 2015) - See, Isaac; Bagchi, Suparna; Booth, Stephanie; Scholz, Daniel; Geller, Andrew I.; Anderson, Lydia; Moulton-Meissner, Heather; Finks, Jennie L.; Kelley, Karen; Gould, Carolyn V.; Patel, Priti R.
<x content-type="archive" xml:space="preserve">Abstract</x> Investigation of an outbreak of Clostridium difficile infection (CDI) at a hemodialysis facility revealed evidence that limited intrafacility transmission occurred despite adherence to published infection control standards for dialysis clinics. Outpatient dialysis facilities should consider CDI prevention, including environmental disinfection for C. difficile, when formulating their infection control plans. Infect. Control Hosp. Epidemiol. 2015;36(8):972–974